-7n-4(6-4n)=-39+4n

Simple and best practice solution for -7n-4(6-4n)=-39+4n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7n-4(6-4n)=-39+4n equation:


Simplifying
-7n + -4(6 + -4n) = -39 + 4n
-7n + (6 * -4 + -4n * -4) = -39 + 4n
-7n + (-24 + 16n) = -39 + 4n

Reorder the terms:
-24 + -7n + 16n = -39 + 4n

Combine like terms: -7n + 16n = 9n
-24 + 9n = -39 + 4n

Solving
-24 + 9n = -39 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
-24 + 9n + -4n = -39 + 4n + -4n

Combine like terms: 9n + -4n = 5n
-24 + 5n = -39 + 4n + -4n

Combine like terms: 4n + -4n = 0
-24 + 5n = -39 + 0
-24 + 5n = -39

Add '24' to each side of the equation.
-24 + 24 + 5n = -39 + 24

Combine like terms: -24 + 24 = 0
0 + 5n = -39 + 24
5n = -39 + 24

Combine like terms: -39 + 24 = -15
5n = -15

Divide each side by '5'.
n = -3

Simplifying
n = -3

See similar equations:

| 20=500-60m | | -5(8m-4)=260 | | 8+.4x=4.4 | | 100=2(2+6k) | | 2+5y-y=y-2+25 | | 86=2(8m-5) | | 3(x+14)+4(x+7)=-35 | | 8-4v=-5(v+4)+5v | | 206=x+7x | | 206=x+(x+7) | | -18+2x=8(6x-8) | | 60=10x+10 | | 3x+2(3x+1)=11 | | 49/70=x/100 | | 15.83=5.95p | | 5+3(7x-9)-4x=-9-.667x+7 | | 3x^3-20x-24=0 | | -0.5(12v-20)+4=-12-8v | | -10x-5y=5 | | 3x+14=x-20 | | 2x-1x+10x= | | 3a+2b-6c= | | 10x+20=8x | | x/60=80/100 | | 2x-3+6x+7=180 | | 570=30-2(2x) | | 392=43x+55x | | 41=12+7 | | x^2-100=(x+10)(x-10) | | 1+2y+2=y-1+10 | | a+b+c+2c= | | -11+14x+2x^2=0 |

Equations solver categories